2014
DOI: 10.1136/thoraxjnl-2014-206260.124
|View full text |Cite
|
Sign up to set email alerts
|

S118 Incidence And Severity Of Chronic Thromboembolic Pulmonary Hypertension Following The Introduction Of A One-stop Clinic For Acute Pulmonary Embolism

Abstract: Background The incidence of malignant pleural effusions (MPE) is increasing and overall prognosis remains poor. In-dwelling pleural catheters (IPCs) relieve symptoms, but increase the risk of pleural infection. We reviewed survival times of cases of pleural infection in patients with IPCs for MPE from 6 UK centres. Methods Baseline data were collected for all IPC insertions from 1/1/05 to 31/1/14. Survival times were analysed by underlying tumour. Results were compared with national data, and with data from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In five other studies, echocardiography was only performed if dyspnoea was reported by the individual patients [7,17,30,31,46]. One study applied the need for further investigation based on a not-further-defined clinical assessment prior to RHC [22]. Three studies targeted patients with a first PE (595 patients in total) [17,44,50] and one study included 87 patients with recurrent VTE only [18].…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In five other studies, echocardiography was only performed if dyspnoea was reported by the individual patients [7,17,30,31,46]. One study applied the need for further investigation based on a not-further-defined clinical assessment prior to RHC [22]. Three studies targeted patients with a first PE (595 patients in total) [17,44,50] and one study included 87 patients with recurrent VTE only [18].…”
Section: Included Studiesmentioning
confidence: 99%
“…The weighted pooled incidence of CTEPH in the all comers was 0.56% (95% CI 0.13-0.98; I 2 =98.3%). Four studies focused on unselected consecutive patients who were alive after an initial treatment period of at least 3 months [22,30,31,35]. The weighted pooled incidence of CTEPH in these 999 survivors followed for a period varying from 3 months to 8 years was 3.2% (95% CI 2.0-4.4; I 2 =7.0%).…”
Section: Included Studiesmentioning
confidence: 99%
“…The incidence of CTEPH is acknowledged to be under-reported at 3-6 ppm per year with a prevalence of 26-38 ppm. [8][9][10] Globally, the causes of PH can differ signifi cantly, with cases of PH related to sickle cell disease and infectious diseases (HIV, schistosomiasis, post-Streptococcus rheumatic heart disease) more prevalent in countries where these are still endemic. 7 In the UK, the mean age at diagnosis of idiopathic pulmonary arterial hypertension (IPAH) is 60 years old, and 37.7% of IPAH patients are male.…”
Section: Clinical Classifi Cationmentioning
confidence: 99%